(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This article examines the place of ancient Turkic stone statues within the system of symbols of Uzbek statehood, based on a comprehensive historical-semiotic analysis. The study analyzes the political-ideological, religious-ritual, and legal-territorial significance of the stone statues, substantiating that they are not merely memorial monuments, but material expressions of the ideology of the Turkic Khaganate. It demonstrates the iconographic and ideological interconnections among stone statues, coins, and tamgas, which constituted the components of the symbolic system existing in the territory of Uzbekistan during the 6th–8th centuries AD.